First Reported Case of Neuroleptospirosis Complicated With Anton's Syndrome - Saeed, Nasheeda; Khoo, Ching Soong; Remli, Rabani; Law, Zhe Kang; Periyasamy, Petrick; Osman, Syazarina Sharis; Tan, Hui Jan (Frontiers in Neurology, 2018)
Abstract Leptospirosis is a spirochetal zoonotic disease with a wide clinical spectrum, often underdiagnosed especially when presented as an acute neurological manifestation. We report a case of a 24-year-old man with serologically positive leptospirosis, who presented with altered sensorium, seizures and subsequently developed cortical blindness. His brain MRI revealed bilateral occipital and later parietal lobe cerebritis.